2017
DOI: 10.1016/j.scs.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent hybrid short-term load forecasting model for smart power grids

Abstract: Highlights 1. A novel hybrid heuristic search optimization based neural network model is proposed for short term load forecast (STLF). 2. Study, analyze and selection of highly correlated historical load and weather variables based on load demand study. 3. Global best Particle swarm optimization (GPSO) is used to update the weight biase values of feedforward neural network. 4. The proposed PSO based NN forecast model is compared to contemporary techniques such as back propagation (BP) and Levenberg marquardt (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 30 publications
(31 reference statements)
0
21
0
2
Order By: Relevance
“…This phenomenon shows variations in load curve and peak hour of the entire system. Moreover, the impact of climatic conditions on the load demand in summers is usually more than other time of year [74]. Figure 2 illustrates the load curves for Thursday as an example.…”
Section: Distribution Of Historic Load Datamentioning
confidence: 99%
“…This phenomenon shows variations in load curve and peak hour of the entire system. Moreover, the impact of climatic conditions on the load demand in summers is usually more than other time of year [74]. Figure 2 illustrates the load curves for Thursday as an example.…”
Section: Distribution Of Historic Load Datamentioning
confidence: 99%
“…In this category, articles are presented like BPNN (Li et al [23]), WTBPNN (Changhao et al [24]), GNBPNN (Irani et al [25]), NNPSO (Zhaoyu et al [26]), WT-ANFIS (Karthika et al [27]), ADE-BPNN (Wang et al [28]), Wavelet-PSO-ANFIS,) Catalao et al [29]), and WT-PSO-BPNN (Mandel et al [30]) whose goal is to arrive at the highest accuracy in forecasting. Some other research are found in [10,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Figure 1 shows the development of the new technique.…”
Section: Introductionmentioning
confidence: 99%
“…The balance of the electrical network and the optimal control of the accumulation system passes through an accurate forecast of load and generation in the network. Load prediction is essential for the efficient and reliable operation of power supply systems, leading to continuous consumer power supply [6]. the PV plant, which according to the forecasting technique used, can receive different types of weather variables as input, which in turn are the output of some Numerical Weather Prediction (NWP) models.…”
Section: Introductionmentioning
confidence: 99%